1991
DOI: 10.3171/jns.1991.74.3.0407
|View full text |Cite
|
Sign up to set email alerts
|

Acute regional cerebral blood flow changes caused by severe head injuries

Abstract: To evaluate the changes in cerebral blood flow (CBF) that occur immediately after head injury and the effects of different posttraumatic lesions on CBF, 61 CBF studies were obtained using the xenon-computerized tomography method in 32 severely head-injured adults (Glasgow Coma Scale score (GCS) less than or equal to 7). The measurements were made within 7 days after injury, 43% in the first 24 hours. During the 1st day, patients with an initial GCS score of 3 or 4 and no surgical mass had significantly lower f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
150
5
8

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 384 publications
(175 citation statements)
references
References 34 publications
12
150
5
8
Order By: Relevance
“…In patients with compromised CBF, further reduction could affect the CMR O 2 . Abnormally low CBF is a common finding in patients with severe traumatic brain injury (Glasgow Coma Scale less than 8; Cold, 1989;Marion et al, 1991;Obrist et al, 1979;Overgaard et al, 1981) and hypoxia may be the single most important secondary factor affecting the outcome in these patients (Miller, 1985). Therefore, indomethacin should be used with care in the acute management of traumatic brain injury, especially in conditions of a high intracranial pressure.…”
Section: Safety Of Indomethacinmentioning
confidence: 99%
“…In patients with compromised CBF, further reduction could affect the CMR O 2 . Abnormally low CBF is a common finding in patients with severe traumatic brain injury (Glasgow Coma Scale less than 8; Cold, 1989;Marion et al, 1991;Obrist et al, 1979;Overgaard et al, 1981) and hypoxia may be the single most important secondary factor affecting the outcome in these patients (Miller, 1985). Therefore, indomethacin should be used with care in the acute management of traumatic brain injury, especially in conditions of a high intracranial pressure.…”
Section: Safety Of Indomethacinmentioning
confidence: 99%
“…Disturbances in cerebral blood flow (CBF are also a common sequela of head injury and have been documented both experimentally (Yamakami and McIntosh, 1991;Bryan et al, 1995;Kochanek et al, 1995;Forbes et al, 1997;Hendrich et al, 1999;Lythgoe et al, 2003) and clinically (Bouma et al, 1991;Marion et al, 1991;Martin et al, 1997;Coles et al, 2002). CBF abnormalities have been shown to be an important mechanism underlying secondary brain damage experimentally (Jenkins et al, 1989;Giri et al, 2000) and clinically have been shown to be strongly associated with poor outcome (Robertson et al, 1992).…”
mentioning
confidence: 99%
“…18,26) Hyperemia in our case was interpreted as the benign hemispheric type induced by metabolic recovery from the damage done by the mild contusional and subdural hematomas. The benign type of hyperemia is considered to be secondarily induced by metabolic demands on the release of metabolic mediators during reestablishment of membrane ionic homeostasis after head injury.…”
Section: Discussionmentioning
confidence: 70%
“…5,12,[18][19][20]22,23,26,30) Complete neuroimaging examinations including CT and MR imaging, cerebral angiography, and SPECT during the period of neurological deterioration found no traces of vasospasm.…”
Section: Discussionmentioning
confidence: 99%